Mucinous Tubular and Spindle Cell Carcinoma of Kidney: A Case Report of a Rare Tumor - Pranesdha Putra, Antonius Galih; Indrawan, Taufik (Riviera Publishing, 2023)
The objective of this research is to enhance the understanding and recognition of Mucinous Tubular and Spindle Cell Carcinoma of the Kidney (MTSCC-K), a rare renal tumor occurring in less than 1% of all renal tumors. The focus is on improving clinical diagnosis, understanding the tumor's characteristics, and exploring the prognosis and implications for patients. The method used in this research is a case study. The results of this research indicate that Clinical Presentation: MTSCC-K predominantly occurs in women and often presents with flank pain, similar to other renal tumors. However, it may lack other typical symptoms such as significant weight loss or urinary problems. Imaging Characteristics: CT scans may reveal solid masses with patchy calcification, often protruding outside the renal contour. These specific imaging features can aid in the differential diagnosis of MTSCC-K Histopathological Features: MTSCC-K is characterized by small, elongated cords or tubules arranged densely, with interspersed myxoid stroma. The presence of slender tubular spindle cell-like structures is a distinctive feature Prognosis: Patients with MTSCC-K, especially when diagnosed early and treated with radical nephrectomy, have a comparatively good prognosis compared to other renal cell carcinomas. The lack of identified metastases in the presented case also supports a positive prognosis. Implications of this research include: Increased awareness among doctors and radiologists about the unique clinical and imaging features of MTSCC-K can lead to faster and more accurate diagnoses.